Distribución espacial y temporal de incendios de la Provincia de Chimborazo utilizando datos de sensores remotos - Cunalata Villagómez, Marlon Ramiro (2021)
Forest fires have been a growing problem in recent years. The historical knowledge of forest fires allows the efficient management of fire in nature. This research aims to study the spatial and temporal distribution of burned areas as an indicator of forest fires in the province of Chimborazo from 2001 to 2019. The satellite product MCD64A1 version 6 was used, determining the burned area and its date of occurrence. The processing was carried out in the geospatial platform Google Earth Engine, generating scripts for replication in other areas. The analysis was carried out inter and intra-annually at different levels: province, town, protected areas, forest/ecosystem, and hydrographic basins. A total of 363 burned area indicator pixels were identified, with a total area affected of 9,084.8 ha. The year 2012 identified the largest area of burned area with 2,650 ha, and the most affected town was Colta, with 4,647 ha, while the most affected ecosystem was ‘Herbazal de Páramo’ with 3,566 ha. The Chimborazo Fauna Production Reserve had the most affected burned area with 316.75 ha compared to Sangay National Park with 87.5 ha. The analysis carried out in the province of Chimborazo with the MCD64A1 product generates a record of historical information that will be useful for integrated fire management, demonstrating that geospatial resources are key to record areas affected by fires